Case report: Intensive online trauma treatment combining prolonged exposure and EMDR 2.0 in a patient with severe and chronic PTSD - Matthijssen, Suzy J. M. A.; Menses, Sophie D. F. (Frontiers in Psychiatry, 2024)
Introduction. Short and intensive trauma treatment programs seem promising in treating post-traumatic stress disorder (PTSD). However, little is known about the effects performing these types of intensive treatment programs online. Method. At the Altrecht Academic Anxiety Centre, an in person intensive trauma focused treatment of six days (three consecutive days in two weeks) was altered into a fully online treatment. A treatment day consisted of 90 minutes of prolonged exposure, 60 minutes of exercise, 90 minutes of Eye Movement Desensitization and Reprocessing (EMDR) 2.0 and 60 minutes of psychoeducation. Mary, a patient diagnosed with chronic and severe PTSD, chronic depressive disorder (single episode, moderate to severe), a panic disorder, and an other specified personality disorder was the first patient to take part in this intensive online trauma treatment. Results. Mary reached full remission of PTSD. The PTSD symptoms (measured on both the clinician-administered PTSD scale for DSM-5, CAPS-5 and The PTSD Checklist for DSM-5, PCL-5) showed maximum improvement and were completely absent during one month and six month follow-up. Moreover, she no longer suffered from severe depressive symptoms and did not report any general psychiatric symptoms (measured with the Beck Depression Inventory version 2, BDI-II and the Brief Symptom Inventory, BSI). Conclusion. In conclusion, the case-report demonstrates that intensive trauma treatment online was successful in this specific case, thereby being a ‘proof of concept’ that intensive trauma treatment online is feasible. It might be promising for patients with severe and chronic PTSD and comorbid psychiatric disorders. However, further research much show if the results of this specific case can be translated to other patients with severe and chronic PTSD and comorbid psychiatric disorders.